Preferential solvation of indomethacin in 1,4-dioxane + water mixtures according to the inverse Kirkwood–Buff integrals method (2023)
ABSTRACT: The preferential solvation parameters (dx1,3) of indomethacin (IMC) in 1,4-dioxane + water binary mixtures were derived from their thermodynamic properties by means of the inverse Kirkwood–Buff integrals method. dx1,3 is negative in water-rich and 1,4-dioxane-rich mixtures but positive in cosolvent compositions from 0.17 to 0.69 in mole fraction of 1,4-dioxane at 298.15 K. It is conjecturable that in water-rich mixtures, the hydrophobic hydration around the aromatic and methyl groups of the drug plays a relevant role in the solvation. The higher solvation by 1,4-dioxane in mixtures of similar cosolvent compositions could be mainly due to polarity effects. Finally, the preference of this drug for water in 1,4-dioxane-rich mixtures could be explained in terms of the higher acidic behavior of water molecules interacting with the hydrogen-acceptor groups present in IMC. © 2015 Taylor & Francis.